2021
DOI: 10.1161/strokeaha.120.029292
|View full text |Cite
|
Sign up to set email alerts
|

Thrombus Migration and Fragmentation After Intravenous Alteplase Treatment

Abstract: Background and Purpose: There is interest in what happens over time to the thrombus after intravenous alteplase. We study the effect of alteplase on thrombus structure and its impact on clinical outcome in patients with acute stroke. Methods: Intravenous alteplase treated stroke patients with intracranial internal carotid artery or middle cerebral artery occlusion identified on baseline computed tomography angiography and with follow-up vascular imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 29 publications
7
44
3
Order By: Relevance
“…12,16,17 The effect of early reperfusion on good outcome was maintained even after adjustment for the final eTICI score, suggesting that its benefit mainly lies in the shorter ischemia duration of the reperfused tissue, better collateral blood flow from recanalized vessels, or less hemorrhagic complications, rather than solely in improvement of postprocedural eTICI scores. [16][17][18] In fact, our results showed that, despite higher rates of ≥2a reperfusion and nominally higher final eTICI ≥2b rates on the last angiographic run, complete reperfusion (final eTICI 3) rates were lower in patients with early reperfusion. This is in line with a previous study by Alves et al, 17 who suggested that the occurrence of early reperfusion or thrombus migration may render it more challenging for the neurointerventionalist to achieve complete reperfusion, since early reperfusion could convert an M1 segment occlusion, which is relatively easy to access, into several more distal occlusions, which are much more difficult to treat by endovascular means.…”
Section: Discussionmentioning
confidence: 99%
“…12,16,17 The effect of early reperfusion on good outcome was maintained even after adjustment for the final eTICI score, suggesting that its benefit mainly lies in the shorter ischemia duration of the reperfused tissue, better collateral blood flow from recanalized vessels, or less hemorrhagic complications, rather than solely in improvement of postprocedural eTICI scores. [16][17][18] In fact, our results showed that, despite higher rates of ≥2a reperfusion and nominally higher final eTICI ≥2b rates on the last angiographic run, complete reperfusion (final eTICI 3) rates were lower in patients with early reperfusion. This is in line with a previous study by Alves et al, 17 who suggested that the occurrence of early reperfusion or thrombus migration may render it more challenging for the neurointerventionalist to achieve complete reperfusion, since early reperfusion could convert an M1 segment occlusion, which is relatively easy to access, into several more distal occlusions, which are much more difficult to treat by endovascular means.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is an increased risk of clot migration, distal migration that hampers MT recanalization scores, and an increased risk of ICH. On the other hand, IV alteplase has shown effectiveness in distal MCA occlusion as well as facilitation of MT with thrombolysis of clot fragments during stent retrieval [55]. Recent randomized trials have improved our understanding of the optimal treatment algorithm.…”
Section: Special Considerations In Thrombectomy Treatment and Combination Therapymentioning
confidence: 99%
“…23 There is an ongoing debate on the use of IVT before MT, proponents of which feel may favorably alter clot properties to facilitate removal, lyse distal thrombi, and theoretically lead to higher first-pass effect rates and successful reperfusion. 24 However, it may also lead to clot fragmentation and render a patient ineligible for MT due to distal migration. On the other hand, dMT may allow faster door-to-groin-puncture times.…”
Section: Discussionmentioning
confidence: 99%